Method for preparing multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing method

Printing photonic crystal structures on the fabric through screen printing method solves the problem of cumbersome preparation process in the prior art, and achieving rapid assembly and high stability of multiple anti-counterfeiting patterned photonic crystal structure color-based fabrics.

CN115976856BActive Publication Date: 2025-04-08ZHEJIANG SCI-TECH UNIV

Patent Information

Application Number
CN202310156385.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2025-04-08
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

The preparation process of existing photonic crystal anti-counterfeiting technology is cumbersome, making it difficult to achieve rapid assembly and industrial production.

Method used

Multiple anti-counterfeiting patterned photonic crystal structures are printed on the fabric by screen printing. By preparing nano microsphere color paste and ultraviolet fluorescent printing paste, combined with screen printing method and heating treatment, the stable curing of the photonic crystal structure is achieved.

Benefits of technology

It realizes the rapid and flexible printing of photonic crystal structure color patterns with multiple anti-counterfeiting effects on fabrics, improving the stability of photonic crystal structure and the feasibility of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115976856B_ABST
    Figure CN115976856B_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-forming fabric by a screen printing method. The method comprises the following steps: S1, preparing a high-mass fraction nano-microsphere color paste and an ultraviolet fluorescent printing color paste for structural coloring; S2, applying a screen printing method to scrape the ultraviolet fluorescent printing color paste on the surface of a hydrophobic fabric to prepare a first ultraviolet fluorescent anti-counterfeiting pattern with anti-counterfeiting information; S3, scraping the slurry on the surface of the hydrophobic fabric with the first ultraviolet fluorescent anti-counterfeiting pattern obtained in S2 by a screen printing method to prepare a hydrophilic transparent pattern base layer and completely cover the first ultraviolet fluorescent anti-counterfeiting pattern; S4, scraping the high-mass fraction nano-microsphere color paste on the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern; S5, heating the fabric on which the nano-microsphere color paste is scraped obtained in S4 to obtain the multi-anti-counterfeiting patterned photonic crystal structure color-forming fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a photonic crystal anti-counterfeiting pattern, in particular to a method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by a screen printing method, and belongs to the technical field of printing and dyeing. Background Art

[0002] Counterfeit and substandard products are a long-standing and increasingly serious global problem, as they have a serious negative impact on the reputation of companies, human health, and the normal order of economic development. Therefore, it is crucial to develop safer, more confidential, and environmentally friendly anti-counterfeiting technologies to effectively combat counterfeiting.

[0003] Photonic crystal (PC) is a crystalline material formed by two or more media with different dielectric constants arranged in a certain period in space. Due to its unique iridescence effect given by its own structure, this feature makes it widely used in the field of anti-counterfeiting. Researchers have combined ultraviolet fluorescent responsive substances with photonic crystals and carried out patterning, further strengthening the development of photonic crystals in the field of anti-counterfeiting. Gao et al. (Gao Z, Chao H, Yang D, et al. Dual-mode multicolored photonic crystal patterns enabled by ultraviolet-responsive core-shell colloidal spheres [J]. Dyes and Pigments, 2018, 148: 108–117.) used semi-continuous emulsion polymerization to prepare ultraviolet (UV) responsive colloidal microspheres. During the synthesis process, the fluorescent precursor with carbamate groups was locally confined in the prepared spherical shell, and then a mask was applied on the substrate surface to spray and prepare a 2D multicolor PC pattern. Ultraviolet light irradiation can induce photodecomposition of carbamate groups in fluorescent precursors and produce amino groups. The prepared patterned photonic crystals can be treated with fluorescent amines to show fluorescence. These novel PC patterns not only show fluorescence, but also have obvious structural colors, and have multiple anti-counterfeiting effects. Tao et al. (Tao J, Lux. Tetraphenylbenzene-modified photonic crystal structure color coating on fabric substrates for dual-mode anti-counterfeiting. Physicochemical and Engineering Aspects, 2022, 655: 0927-7757.) The surface of SiO2 colloid spheres is modified by aggregation-induced emission of organic molecules (AIE), and then vertically deposited on a polyester fabric substrate to which a mask is applied. The modified SiO2 colloid spheres are self-assembled into PC coatings. The PC coating not only presents a dazzling structural color due to the Bragg diffraction law, but also presents a pigment color due to the AIE fluorescence effect under ultraviolet irradiation, which has a good anti-counterfeiting effect. The above preparation technologies all modify nano-microspheres to make them ultraviolet fluorescent responsive, but the preparation process of microspheres is relatively cumbersome, and it is difficult to achieve rapid assembly effect by vertical deposition assembly method to construct photonic crystal patterns, making it difficult to achieve industrial production of anti-counterfeiting products. If ultraviolet fluorescent responsive substances can be directly combined with patterned photonic crystal preparation technology, patterned photonic crystal structure color-forming fabrics with multiple anti-counterfeiting functions can be prepared more simply and efficiently, which will undoubtedly help promote the application and development of photonic crystal structure color-forming technology in textile printing and dyeing and anti-counterfeiting fields. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by a screen printing method, which can flexibly and quickly print a photonic crystal structure color-producing pattern with high structural stability and multiple anti-counterfeiting effects on the fabric.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by a screen printing method, the method comprising the following steps:

[0007] S1. Preparation of high-quality nano-microsphere color paste and UV fluorescent printing color paste for structural color generation

[0008] The nano-microsphere color paste is prepared by mixing nano-microsphere dispersion, melanin and surfactant, wherein the mass fraction of nano-microspheres in the nano-microsphere dispersion is 36-50%, the melanin is 0.04-0.2% of the weight of the nano-microsphere dispersion, and the surfactant is 1-3% of the weight of the nano-microsphere dispersion;

[0009] The nanospheres are selected from any one of organic polymer polymethyl methacrylate (PMMA) nanospheres, polystyrene (PS) nanospheres, poly(styrene-methyl methacrylate) (P(St-MMA)), poly(styrene-hydroxyethyl acrylate) (P(St-HEA)), poly(styrene-methacrylic acid) (P(St-MAA)), polystyrene@polydopamine (PS@PDA), polystyrene@silicon dioxide (PS@SiO2) or inorganic silicon dioxide (SiO2) nanospheres;

[0010] The ultraviolet fluorescent printing paste is prepared by mixing an ultraviolet fluorescent response substance, a synthetic thickener and a soft segment and hard segment copolymerized waterborne polyurethane, wherein the amount of the ultraviolet fluorescent response substance is 6-10% by weight of the waterborne polyurethane, and the amount of the synthetic thickener is 0.5-1.0% by weight of the waterborne polyurethane;

[0011] The ultraviolet fluorescent response substance is selected from fluorescent disperse dyes, fluorescent brighteners or fluorescein;

[0012] Waterborne polyurethane is added in the form of an aqueous dispersion with a mass fraction of 45-55%;

[0013] S2, applying a screen printing method to scrape ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to prepare an ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information;

[0014] S3, printing the slurry on the surface of the hydrophobic fabric having the first ultraviolet fluorescent anti-counterfeiting pattern obtained in S2 by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the first ultraviolet fluorescent anti-counterfeiting pattern;

[0015] The coating of the transparent pattern base layer is mixed with a synthetic thickener, a soft segment and hard segment copolymerized waterborne polyurethane or waterborne polyacrylate, and a hydrophilic substance, wherein the amount of the synthetic thickener is 0.5-1.0% of the weight of the waterborne polyurethane or waterborne polyacrylate, and the amount of the hydrophilic substance is 0.5-2.5% of the weight of the waterborne polyurethane or waterborne polyacrylate.

[0016] The soft segment and hard segment copolymerized waterborne polyurethane or waterborne polyacrylate is added in the form of water dispersion, with a mass fraction of 45-55%.

[0017] The hydrophilic substance is one or a mixture of glycerol, ethylene glycol, propylene glycol, and urea;

[0018] S4, applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0019] S5. Heat the fabric obtained in S4 to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer, the secondary curing inside the photonic crystal structure, and the stable curing of the photonic crystal structure, so as to obtain a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0020] Preferably, in S2, the screen printing process is: a rubber scraper is used to scrape and print twice on a 100-150 mesh screen, dried at 80-90°C, and baked at 140-150°C for 1-2 minutes to obtain a UV fluorescent first anti-counterfeiting pattern with anti-counterfeiting information.

[0021] The best option is: scrape the 120-mesh screen twice with a rubber scraper, dry at 80°C, and bake at 140°C for 2 minutes. Under this condition, the uniformity and fineness of the UV fluorescent first anti-counterfeiting pattern are better.

[0022] Preferably, in S3, the screen printing process is: a rubber scraper is used to scrape and print twice on a 100-150 mesh screen, dried at 80-90°C, and baked at 120-130°C for 1-2 minutes, and the prepared transparent pattern base layer completely covers the first anti-counterfeiting pattern.

[0023] The best choice is: scrape the 120 mesh screen twice with a rubber scraper, dry at 80℃, and bake at 120℃ for 1 minute. Under this condition, the transparent pattern base layer has good uniformity and fineness, and the surface contact angle is low, which has good hydrophilicity.

[0024] Preferably, the nano-microspheres have a diameter of 150-350 nm, good sphericity, and a monodispersity index of less than 0.08.

[0025] Preferably, the heating treatment conditions in S5 are: temperature 50-70° C., humidity 50-70%, and time 3-60 min.

[0026] The best choice is: temperature 60℃, humidity 60%, time 30min. Under this condition, the nano-microspheres are oriented under sufficient thermal driving force, and the arrangement time is long, and the regularity of assembly is good.

[0027] Preferably, the fabric is a natural fiber or a synthetic fiber or a blended fabric of several of them, the natural fiber includes cotton, linen, silk or wool, the synthetic fiber includes polyester, nylon, spandex, polypropylene, acrylic, polylactic acid or carbon fiber, and the fabric is subjected to hydrophobic finishing;

[0028] The hydrophobic finishing process is: the fabric is immersed in a silicon-containing hydrophobic finishing agent or a fluorine-containing hydrophobic finishing agent at a concentration of 4-6% (owf) and a bath ratio of 1:15-25 for 15-20 minutes, squeezed dry, dried at 80-90°C, and baked at 140-150°C for 1-2 minutes to obtain a highly hydrophobic fabric.

[0029] The best choice is: 5% fluorine-containing water-repellent finishing agent concentration (owf), bath ratio 1:20, immersion treatment of fabric for 18 minutes, squeeze dry, dry at 90℃, and bake at 140℃ for 2 minutes. The surface contact angle of the fabric treated under this condition is the highest, and it has good hydrophobic properties.

[0030] Preferably, the soft segment and hard segment copolymerized waterborne polyurethane, the hard segment is selected from one of toluene diisocyanate, isophorone diisocyanate, and 1,6-hexamethylene diisocyanate; the soft segment is a long carbon chain soft material with crystalline properties, the carbon chain length in the repeating unit is more than 4 C, and the soft segment is selected from one of poly(1,4-butylene adipate), poly(1,6-hexanediol adipate), and poly-1,6-hexamethylene carbonate;

[0031] The soft segment and hard segment copolymerized water-based polyacrylate has a hard segment selected from one of methyl methacrylate, hydroxyethyl methacrylate or methyl acrylate, and a soft segment is a long straight-chain monomer with more than 4 carbon atoms, selected from one of butyl acrylate, n-pentyl acrylate, n-hexyl acrylate and isooctyl acrylate.

[0032] Preferably, the melanin is carbon black, water-soluble melanin or a mixture of several of them.

[0033] Preferably, the surfactant is one or a mixture of polyoxyethylene sorbitan fatty acid ester, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty acid methyl ester ethoxylate or ethylene oxide adduct of polypropylene glycol.

[0034] Preferably, the synthetic thickener is an alkali-resistant and salt-resistant acrylonitrile synthetic thickener, and the synthetic thickener commonly used in the field for printing paste can be selected, mainly satisfying the alkali-resistant and salt-resistant properties.

[0035] Preferably, in S1, the components of the nano-microsphere printing paste and the ultraviolet fluorescent printing paste are mixed and then magnetically stirred at a speed of 20 r / s for 10 minutes to make them uniformly mixed.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared by the present invention selectively reflects under sunlight due to the existence of the photon bandgap, presenting a structural color pattern, and the color changes with the change of the observation angle, and no fluorescent anti-counterfeiting pattern hidden underneath appears, and only the photonic crystal pattern with obvious angle dependence is displayed. Under ultraviolet light irradiation, the photonic crystal pattern has no selective reflection of visible light, and the human eye perceives it as black, while the fluorescent substance on the bottom layer of the pattern shows an obvious fluorescent effect under the action of ultraviolet light. This method can achieve the dual anti-counterfeiting effects of the iridescent effect pattern of the photonic crystal itself that changes with the angle under sunlight and the fluorescent pattern displayed under ultraviolet light irradiation.

[0038] 2. The preparation of conventional anti-counterfeiting patterned photonic crystals requires modification of nano-microspheres to make the microspheres themselves responsive, and the preparation method is relatively cumbersome. The present invention physically combines anti-counterfeiting fluorescent patterns and photonic crystal patterns to have multiple anti-counterfeiting effects, and the screen printing method can be used to simply and conveniently print fine patterns, so that anti-counterfeiting fluorescent patterns with fine coding information can be easily obtained, and patterned photonic crystals can also be quickly constructed, which not only makes patterned photonic crystals with iridescent effects have large-area, fast, and flexible industrialization prospects for preparation, but also further promotes the development of photonic crystal structure color technology in the field of anti-counterfeiting.

[0039] 3. The patterned hydrophilic polymer layer constructed on the fabric surface of the present invention can undergo interfacial activation and interfacial polymer migration (from the base layer to the photonic crystal layer) during the assembly process and produce secondary solidification inside the photonic crystal, playing the role of "ligament" between the nano-microspheres, the structural units of the photonic crystal, thereby improving the photonic crystal structure's ability to withstand external forces (friction, bending, washing, etc.), thereby significantly improving the stability of the photonic crystal structure and facilitating the retention of the refractive index difference inside the photonic crystal. The use of a high-concentration nano-microsphere dispersion as the main body of the scraping color paste is conducive to the rapid assembly of the nano-microspheres into an ordered photonic crystal structure on the fabric surface. The brightness and saturation of the photonic crystal structure color are relatively high, achieving high stability and high saturation consistency of the multi-anti-counterfeiting photonic crystal structure color-producing fabric. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic diagram of the process of preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by the screen printing method in Example 1;

[0041] Figure 2 The contact angle test results of the hydrophobic finished fabric and the hydrophilic pattern substrate layer prepared by screen printing method in Example 2;

[0042] Figure 3 is a digital picture of the multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared in Example 3 taken under sunlight, wherein a is a sample pattern taken when the angle between the observation angle and the normal is 0°, b is a sample pattern taken when the angle between the observation angle and the normal is 30°, and c is a sample pattern taken when the angle between the observation angle and the normal is 60°;

[0043] Figure 4 This is a digital photo of the multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared in Example 4 taken under ultraviolet light;

[0044] Figure 5 1 is a reflectivity curve (a) and a SEM image (b) of the multiple anti-counterfeiting patterned photonic crystal prepared in Example 5;

[0045] Figure 6 This is the test result of multiple bending of the multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared in Example 6;

[0046] Figure 7 This is a digital photo taken under ultraviolet light of the multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared by adding 2.0 wt% of ultraviolet fluorescent response material in Comparative Example 1;

[0047] Figure 8 This is a digital photo of comparative example 2 after using 28wt% nano-microsphere dispersion as the scraping color paste;

[0048] Fig. 9 This is a digital photo of comparative example 3 after using 56wt% nano-microsphere dispersion as the scraping color paste;

[0049] Fig.10 These are the results of multiple bending tests on the multi-anti-counterfeiting patterned photonic crystal structure colored fabric prepared in Example 4 with no high molecular polymer added to the hydrophilic pattern base layer. DETAILED DESCRIPTION

[0050] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0051] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0052] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, if not otherwise specified, can all be obtained from commercial channels).

[0053] Sources of reagents in the following examples:

[0054] Hydrophobic finishing agent: fluorine-containing water-repellent finishing agent, silicon-containing water-repellent finishing agent, Zhejiang Chuanhua Co., Ltd.; (list some, but not limited to the above products).

[0055] Colloidal nanosphere dispersion, laboratory homemade, taking the preparation method of PS nanosphere as an example: 1000g deionized water, 450g styrene (St) are added to a 3000mL four-mouth round-bottom flask with mechanical stirring and condensing device, followed by adding 0.75g sodium dodecyl sulfate (SDS), stirring speed is 350rpm, when the temperature rises to 85°C, 1.05g potassium persulfate is dissolved in 50mL deionized water and added to the four-mouth flask. The entire reaction system is carried out under a nitrogen atmosphere and reacts for 4-5h. The above synthesized 30wt% nanosphere dispersion is further evaporated by a rotary evaporator. The obtained dispersion is filtered with a 200-mesh nylon mesh to finally obtain a nanosphere dispersion with a concentration of 36-46wt%.

[0056] Ultraviolet fluorescent response substances: Rhodamine B, fluorescein, Shanghai Yien Chemical Technology Co., Ltd.; Dispersed fluorescent red G, dispersed fluorescent orange 2GFL, dispersed fluorescent yellow 10GN, dispersed fluorescent green 5G, Zhejiang Jihua Group Co., Ltd.; fluorescent brightener CPD-A, Tianjin Yudu Technology Development Co., Ltd.; (listed some, but not limited to the above products).

[0057] Soft segment and hard segment copolymerized polyacrylic acid: water-based polyacrylate, model P1907, model P3904, model P3902s, etc., Zhejiang Chuanhua Co., Ltd.; soft segment and hard segment copolymerized polyurethane: water-based polyurethane, model PUE1650, model PUE-2013, model PUE1401, etc., Shanghai Sisheng Polymer Materials Co., Ltd. (list some, but not limited to the above products). The soft segment and hard segment copolymerized water-based polyurethane or water-based polyacrylate is added in the form of an aqueous dispersion.

[0058] The soft segment and hard segment copolymerized waterborne polyacrylate or polyurethane described in the present invention refers to the large-area preparation method of high-stability and high-saturation photonic crystal structure color-forming fabric in Chinese invention CN114164661A, and a photonic crystal structure color-forming fabric and its preparation method in CN112323495A.

[0059] Example 1

[0060] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, the specific steps are as follows:

[0061] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0062] A PS nanosphere dispersion with a particle size of 232 nm (PS nanosphere mass fraction of 36 wt%), 0.04 wt% carbon black and 1 wt% polyoxyethylene sorbitan fatty acid ester were mixed and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0063] A waterborne polyurethane PUE1401 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 6.0% of rhodamine B and 0.5% of a synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0064] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the cotton fabric is subjected to hydrophobic finishing, and the concentration of the fluorine-containing water-repellent finishing agent is 4%.

[0065] (owf), the fabric was impregnated for 20 min at a bath ratio of 1:25, squeezed dry, dried at 80 ° C, and baked at 140 ° C for 1 min to obtain a highly hydrophobic fabric;

[0066] The ultraviolet fluorescent printing paste is printed on the surface of the cotton fabric by screen printing, and heated and cured to form a film to obtain a fabric with an ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 10 g / m2 (dry weight);

[0067] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the cotton fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 10 g / m2 (dry weight);

[0068] The hydrophilic coating is prepared by mixing a soft segment and hard segment copolymerized waterborne polyacrylate (P1907) with a hydrophilic substance (propylene glycol), wherein the amount of the hydrophilic substance is 0.6 wt % (the same below) of the solid content of the waterborne polyacrylate in the waterborne polyacrylate emulsion (i.e., water dispersion).

[0069] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0070] (5) The coated fabric is placed in an environment of 50°C and 50% humidity for 60 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0071] Example 2

[0072] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, the specific steps are as follows:

[0073] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0074] A PMMA nanosphere dispersion with a particle size of 310 nm (PMMA nanosphere mass fraction of 38 wt%), 0.06% carbon black and 1.5% fatty acid polyoxyethylene ester accounting for the weight of the nanosphere dispersion, are mixed and magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0075] A waterborne polyurethane PUE1650 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 7.0% of the weight of the waterborne polyurethane fluorescein and 0.6% of a synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0076] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester fabric is subjected to hydrophobic finishing, and the concentration of the fluorine-containing water-repellent finishing agent is 5%

[0077] (owf), the fabric was impregnated for 18 min at a bath ratio of 1:20, squeezed dry, dried at 90 ° C, and baked at 140 ° C for 2 min to obtain a highly hydrophobic fabric;

[0078] Ultraviolet fluorescent printing paste is printed on the surface of polyester fabric by screen printing method, and heated and cured to form a film to obtain a fabric with ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 12 g / m2 (dry weight);

[0079] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester fabric by screen printing, and heated and cured to form a film to obtain a fabric with a hydrophilic polymer layer transparent pattern on the surface, and the coating amount is 12 g / m2 (dry weight);

[0080] The hydrophilic coating is a mixture of a soft-segment and hard-segment copolymerized water-based polyacrylate (P3904) and a hydrophilic substance (ethylene glycol), wherein the amount of the hydrophilic substance is 1.0% of the mass of the water-based polyacrylate.

[0081] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0082] (5) The coated fabric is placed in an environment of 50°C and 60% humidity for 45 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0083] Example 3

[0084] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, the specific steps are as follows:

[0085] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0086] A PS@PDA nanosphere dispersion with a particle size of 278 nm (PS@PDA nanosphere mass fraction of 40 wt%) was mixed with 0.02% carbon black and 1.8% fatty alcohol polyoxyethylene ether by weight of the nanosphere dispersion, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0087] A waterborne polyurethane PUE-2013 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 8.0% of the dispersed fluorescent red G and 0.7% of the synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0088] (2) Applying the screen printing method to scrape ultraviolet fluorescent printing paste on the surface of hydrophobic fabrics, it is easy to prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester-ammonia blended fabric is subjected to hydrophobic finishing, and the fabric is impregnated for 16 minutes under the conditions of fluorine-containing water-repellent finishing agent concentration of 6% (owf) and bath ratio of 1:15, squeezed dry, dried at 80°C, and baked at 140°C for 1 minute to obtain a highly hydrophobic fabric;

[0089] The ultraviolet fluorescent printing paste is printed on the surface of the polyester-spandex blended fabric by screen printing, and heated and cured to form a film to obtain a fabric with an ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 15 g / m2 (dry weight);

[0090] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester-ammonia blended fabric by screen printing, and heated to cure to form a film to obtain a fabric with a hydrophilic polymer layer transparent pattern on the surface, and the coating amount is 15 g / m2 (dry weight);

[0091] The hydrophilic coating is made of a mixture of a soft-segment and hard-segment copolymerized water-based polyacrylate (P3902s) and a hydrophilic substance (propylene glycol), wherein the amount of the hydrophilic substance is 1.4% of the mass of the water-based polyacrylate.

[0092] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0093] (5) The coated fabric is placed in an environment of 60°C and 60% humidity for 30 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0094] Example 4

[0095] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, the specific steps are as follows:

[0096] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0097] A PS@SiO2 nanosphere dispersion with a particle size of 256 nm (PS@SiO2 nanosphere mass fraction of 46 wt%) was mixed with 0.10% carbon black and 2.0% fatty acid methyl ester ethoxylate by weight of the nanosphere dispersion, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0098] A waterborne polyurethane PUE1650 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 9.0% of the dispersed fluorescent orange 2GFL and 0.8% of the synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0099] (2) Applying the screen printing method to scrape ultraviolet fluorescent printing paste on the surface of hydrophobic fabrics, it is easy to prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester silk fabric is subjected to hydrophobic finishing, and the fabric is impregnated for 19 minutes under the conditions of 4% (owf) of silicon-containing water-repellent finishing agent and 1:25 bath ratio, squeezed dry, dried at 90°C, and baked at 140°C for 1 minute to obtain a highly hydrophobic fabric;

[0100] The ultraviolet fluorescent printing paste is printed on the surface of the silk fabric by screen printing, and heated and cured to form a film to obtain a fabric with an ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 15 g / m2 (dry weight);

[0101] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the silk fabric by screen printing, and heated to cure to form a film, to obtain a fabric with a hydrophilic polymer layer transparent pattern on the surface, and the coating amount is 15 g / m2 (dry weight);

[0102] The hydrophilic coating is a mixture of soft-segment and hard-segment copolymerized waterborne polyurethane (PUE1650) and a hydrophilic substance (urea), wherein the amount of the hydrophilic substance is 1.8% of the mass of the polymer.

[0103] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0104] (5) The coated fabric is placed in an environment of 60°C and 70% humidity for 25 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0105] Example 5

[0106] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, the specific steps are as follows:

[0107] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0108] A P(St-HEA) nanosphere dispersion with a particle size of 273 nm (P(St-HEA) nanosphere mass fraction of 44 wt%), 0.16% of carbon black and 2.2% of ethylene oxide adduct of polypropylene glycol accounting for the weight of the nanosphere dispersion, were mixed, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0109] A waterborne polyurethane PUE1401 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 9.0% of the weight of the waterborne polyurethane dispersed fluorescent yellow 10GN and 0.9% of a synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniformly mixed, and then set aside;

[0110] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester fabric is subjected to hydrophobic finishing, and the concentration of the silicon-containing water-repellent finishing agent is 5%.

[0111] (owf), the fabric was impregnated for 17 min at a bath ratio of 1:20, squeezed dry, dried at 80 °C, and baked at 140 °C for 2 min to obtain a highly hydrophobic fabric;

[0112] Ultraviolet fluorescent printing paste is printed on the surface of polyester fabric by screen printing, and heated and cured to form a film to obtain a fabric with ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 18 g / m2 (dry weight);

[0113] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 18 g / m2 (dry weight);

[0114] The hydrophilic coating is a mixture of soft-segment and hard-segment copolymerized waterborne polyurethane (PUE-2013) and a hydrophilic substance (ethylene glycol), wherein the amount of the hydrophilic substance is 2.0% of the mass of the high molecular weight polymer.

[0115] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0116] (5) The coated fabric is placed in an environment of 70°C and 70% humidity for 5 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0117] Example 6

[0118] A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, the specific steps are as follows:

[0119] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0120] A P(St-MMA) nanosphere dispersion with a particle size of 292 nm (P(St-MMA) nanosphere mass fraction of 42 wt%), 0.18% of carbon black and 2.5% of fatty acid methyl ester ethoxylate accounting for the weight of the nanosphere dispersion, are mixed and magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0121] A waterborne polyurethane PUE-2013 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 10.0% of the fluorescent brightener CPD-A and 1.0% of the synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniformly mixed, and then set aside;

[0122] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester fabric is subjected to hydrophobic finishing, and the concentration of the silicon-containing water-repellent finishing agent is 6%.

[0123] (owf), the fabric was immersed in the bath ratio of 1:15 for 15 minutes, squeezed dry, dried at 90℃, and baked at 140℃ for 1 minute to obtain a highly hydrophobic fabric;

[0124] Ultraviolet fluorescent printing paste is printed on the surface of polyester fabric by screen printing, and heated and cured to form a film to obtain a fabric with ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 20 g / m2 (dry weight);

[0125] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 20 g / m2 (dry weight);

[0126] The hydrophilic coating is a mixture of soft-segment and hard-segment copolymerized waterborne polyurethane (PUE1401) and a hydrophilic substance (propylene glycol), wherein the amount of the hydrophilic substance is 2.2% of the mass of the high molecular weight polymer.

[0127] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0128] (5) The coated fabric is placed in an environment of 70°C and 70% humidity for 7 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0129] Figure 1 It is a schematic diagram of the process of preparing the color-producing fabric with multiple anti-counterfeiting patterned photonic crystal structure by the screen printing method in Example 1. This process can easily and quickly prepare the color-producing fabric with multiple anti-counterfeiting patterned photonic crystal structure.

[0130] Figure 2 The contact angle test results of the hydrophobic finished fabric and the hydrophilic pattern substrate layer prepared by screen printing in Example 2 are as follows: Figure 2 As shown, impregnating the fabric with a hydrophobic finishing agent and heat treating it for a short time can make the fabric surface have strong hydrophobic properties (contact angle: 135.8°), and the transparent pattern of the polymer layer printed by screen printing has good hydrophilic properties (contact angle: 47.5°). It has been verified that the hydrophobic fabrics and hydrophilic polymer layers prepared in Examples 1-6 can achieve the above effects.

[0131] Figure 3 This is a digital picture of the multiple anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared in Example 3 taken under sunlight. The prepared structural color-producing pattern has uniform color without defects, and presents different structural colors at different angles, showing an iridescent effect. It has been verified that the structural color-producing patterns prepared in Examples 1-6 all show obvious angle dependence, that is, an iridescent effect.

[0132] Figure 4This is a digital picture of the multi-anti-counterfeiting patterned photonic crystal structure colored fabric prepared in Example 4 taken under ultraviolet light. The photonic crystals on the prepared "maple leaf" pattern have no green light and can selectively reflect, and the human eye perceives it as black. The fluorescent substance on the QR code pattern shows an obvious fluorescent effect under ultraviolet light and can be effectively scanned by a mobile phone. It has been verified that the ultraviolet fluorescent anti-counterfeiting patterns prepared in Examples 1-6 can achieve the above effects.

[0133] Figure 5 is the reflectivity curve of the photonic crystal prepared in Example 5, such as Figure 5 As shown, the reflectivity peak is high and narrow, and the SEM image also shows that the arrangement of the nanospheres is highly regular, proving that the brightness and saturation of the structural color are high. It has been verified that the photonic crystals prepared in Examples 1-6 all have high brightness and saturation.

[0134] The patterned photonic crystal structure color-producing fabric prepared in Example 6 was bent 5-6 times. Figure 6 This is the test result of multiple bending of the patterned photonic crystal structure color-producing fabric. After multiple bending, the photonic crystal has no damage, proving its excellent structural stability.

[0135] Comparative Example 1

[0136] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0137] A PS nanosphere dispersion with a particle size of 232 nm (PS nanosphere mass fraction of 36 wt%), 0.04 wt% carbon black and 1 wt% polyoxyethylene sorbitan fatty acid ester were mixed and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0138] A waterborne polyurethane PUE1401 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 2.0% of rhodamine B and 0.5% of a synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0139] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the cotton fabric is subjected to hydrophobic finishing, and the concentration of the fluorine-containing water-repellent finishing agent is 4%.

[0140] (owf), the fabric was impregnated for 20 min at a bath ratio of 1:25, squeezed dry, dried at 80 ° C, and baked at 140 ° C for 1 min to obtain a highly hydrophobic fabric;

[0141] The ultraviolet fluorescent printing paste is printed on the surface of the cotton fabric by screen printing, and heated and cured to form a film to obtain a fabric with an ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 10 g / m2 (dry weight);

[0142] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the cotton fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 10 g / m2 (dry weight);

[0143] The hydrophilic coating is prepared by mixing a soft segment and hard segment copolymerized waterborne polyacrylate (P1907) with a hydrophilic substance (propylene glycol), wherein the amount of the hydrophilic substance is 0.6 wt % (the same below) of the solid content of the waterborne polyacrylate in the waterborne polyacrylate emulsion (i.e., water dispersion).

[0144] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0145] (5) The coated fabric is placed in an environment of 50°C and 50% humidity for 60 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0146] Comparative Example 2

[0147] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0148] A PMMA nanosphere dispersion with a particle size of 310 nm (PMMA nanosphere mass fraction of 28 wt%), 0.06 wt% carbon black and 1.5 wt% fatty acid polyoxyethylene ester were mixed, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0149] A waterborne polyurethane PUE1650 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 7.0% of the weight of the waterborne polyurethane fluorescein and 0.6% of a synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0150] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester fabric is subjected to hydrophobic finishing, and the concentration of the fluorine-containing water-repellent finishing agent is 5%

[0151] (owf), the fabric was impregnated for 18 min at a bath ratio of 1:20, squeezed dry, dried at 90 ° C, and baked at 140 ° C for 2 min to obtain a highly hydrophobic fabric;

[0152] Ultraviolet fluorescent printing paste is printed on the surface of polyester fabric by screen printing method, and heated and cured to form a film to obtain a fabric with ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 12 g / m2 (dry weight);

[0153] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 12 g / m2 (dry weight);

[0154] The hydrophilic coating is a mixture of a soft-segment and hard-segment copolymerized water-based polyacrylate (P3904) and a hydrophilic substance (ethylene glycol), wherein the amount of the hydrophilic substance is 1.0% of the mass of the water-based polyacrylate.

[0155] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0156] (5) The coated fabric is placed in an environment of 50°C and 60% humidity for 45 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0157] Comparative Example 3

[0158] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0159] A P(St-MMA) nanosphere dispersion with a particle size of 292 nm (P(St-MMA) nanosphere mass fraction of 56 wt%), 0.18% of carbon black and 2.5% of fatty acid methyl ester ethoxylate accounting for the weight of the nanosphere dispersion, are mixed and magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0160] A waterborne polyurethane PUE-2013 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 10.0% of the fluorescent brightener CPD-A and 1.0% of the synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniformly mixed, and then set aside;

[0161] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester fabric is subjected to hydrophobic finishing, and the concentration of the silicon-containing water-repellent finishing agent is 6%.

[0162] (owf), the fabric was immersed in the bath ratio of 1:15 for 15 minutes, squeezed dry, dried at 90℃, and baked at 140℃ for 1 minute to obtain a highly hydrophobic fabric;

[0163] Ultraviolet fluorescent printing paste is printed on the surface of polyester fabric by screen printing, and heated and cured to form a film to obtain a fabric with ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 20 g / m2 (dry weight);

[0164] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 20 g / m2 (dry weight);

[0165] The hydrophilic coating is a mixture of soft-segment and hard-segment copolymerized waterborne polyurethane (PUE1401) and a hydrophilic substance (propylene glycol), wherein the amount of the hydrophilic substance is 2.2% of the mass of the high molecular weight polymer.

[0166] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0167] (5) The coated fabric is placed in an environment of 70°C and 70% humidity for 7 minutes to complete the assembly of nano-microspheres, the activation and migration of the interface molecules of the polymer layer on the surface of the fabric, and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0168] Comparative Example 4

[0169] (1) Preparation of high-quality nano-microsphere color paste and ultraviolet fluorescent printing color paste for structural color generation:

[0170] A P(St-MMA) nanosphere dispersion with a particle size of 292 nm (P(St-MMA) nanosphere mass fraction of 56 wt%), 0.18% of carbon black and 2.5% of fatty acid methyl ester ethoxylate accounting for the weight of the nanosphere dispersion, are mixed and magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniform, and then set aside;

[0171] A waterborne polyurethane PUE-2013 dispersion (the mass fraction of the waterborne polyurethane is 50 wt%) is mixed with 10.0% of the fluorescent brightener CPD-A and 1.0% of the synthetic thickener, and then magnetically stirred at a speed of 20 r / s for 10 min to make the mixture uniformly mixed, and then set aside;

[0172] (2) Applying the screen printing method to scrape the ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to easily prepare the ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information: firstly, the polyester fabric is subjected to hydrophobic finishing, and the concentration of the silicon-containing water-repellent finishing agent is 6%.

[0173] (owf), the fabric was immersed in the bath ratio of 1:15 for 15 minutes, squeezed dry, dried at 90℃, and baked at 140℃ for 1 minute to obtain a highly hydrophobic fabric;

[0174] Ultraviolet fluorescent printing paste is printed on the surface of polyester fabric by screen printing, and heated and cured to form a film to obtain a fabric with ultraviolet fluorescent anti-counterfeiting pattern on the surface, and the coating amount is 20 g / m2 (dry weight);

[0175] (3) The surface of the hydrophobic fabric with the ultraviolet fluorescent first anti-counterfeiting pattern obtained in S2 is scraped with a slurry by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the ultraviolet fluorescent first anti-counterfeiting pattern: a hydrophilic coating is scraped on the surface of the polyester fabric by screen printing, heated and cured to form a film, and a fabric with a hydrophilic polymer layer transparent pattern on the surface is obtained, and the coating amount is 20 g / m2 (dry weight);

[0176] The hydrophilic coating is made by mixing conventional screen printing paste with a hydrophilic substance (propylene glycol), wherein the amount of the hydrophilic substance is 2.2% of the printing paste.

[0177] (4) applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern;

[0178] (5) The coated fabric is placed in an environment of 70° C. and 70% humidity for 7 minutes to complete the assembly of the nano-microspheres and the stabilization of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric.

[0179] Figure 7 This is a digital picture of the multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric prepared by screen printing in Comparative Example 1 (compared with Example 1) taken under ultraviolet light. Figure 7 It can be seen that the amount of ultraviolet fluorescent response material added is small, and under ultraviolet light irradiation, the clarity of the fluorescent pattern is poor, affecting its anti-counterfeiting effect.

[0180] Figure 8This is a digital photo of a multi-anti-counterfeit patterned photonic crystal structure color-producing fabric prepared by screen printing in Comparative Example 2 (compared with Example 2). Figure 8 It can be seen that when the nano-microsphere dispersion with a lower solid content is used as the scraping color paste, the color brightness and saturation of the prepared structural color pattern are lower.

[0181] Fig. 9 This is a digital photo of a multi-anti-counterfeit patterned photonic crystal structure color-producing fabric prepared by screen printing in Comparative Example 3 (compared with Example 6), Fig. 9 It can be seen that when the nanosphere dispersion with a higher solid content is used as the scraping color paste, the color brightness and saturation of the prepared structural color pattern are better, but due to the large number of stacked layers of the ordered structure of the photonic crystal, the pattern is prone to obvious cracks and the outline clarity is slightly poor (see Fig. 9 ).

[0182] Fig.10 This is an optical photograph of the multiple anti-counterfeiting patterned photonic crystal structure color fabric prepared in Example 4 (compared with Example 6) without adding a high molecular polymer to the hydrophilic pattern base layer after multiple bending. It can be seen that its structural stability is poor and the photonic crystal is prone to irreversible damage under strong external force.

[0183] In summary, the multiple anti-counterfeiting patterned photonic crystal structure color-forming fabric prepared by the present invention selectively reflects under sunlight due to the presence of the photon bandgap, and the color changes with the change of the observation angle, and no fluorescent anti-counterfeiting pattern hidden underneath appears, and only the photonic crystal pattern with obvious angle dependence is displayed. Under ultraviolet light irradiation, the non-visible light on the photonic crystal pattern is selectively reflected, and the human eye feels black, while the fluorescent substance on the bottom layer of the pattern shows an obvious fluorescent effect under the action of ultraviolet light, achieving the dual anti-counterfeiting effect of the iridescent effect of the photonic crystal itself and the fluorescent pattern displayed under ultraviolet light. Through the screen printing method, fine patterns can be printed simply and conveniently, so that anti-counterfeiting fluorescent patterns with fine coding information can be easily obtained, and patterned photonic crystals can also be quickly constructed. By constructing a water-based polyurethane or polyacrylate polymer receiving and stabilizing layer, the structural stability of the multiple anti-counterfeiting patterned photonic crystal structure color-forming fabric and the durability of the structural color are improved.

[0184] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0185] The above is a detailed introduction to the method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by a screen printing method provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a multi-anti-counterfeiting patterned photonic crystal structure color-producing fabric by screen printing, characterized in that The method comprises the following steps: S1. Preparation of high-quality nano-microsphere color paste and UV fluorescent printing color paste for structural color generation The nano-microsphere color paste is mixed with nano-microsphere dispersion, melanin and surfactant, wherein the mass fraction of nano-microspheres in the nano-microsphere dispersion is 36-50%, the melanin is 0.04-0.2% of the weight of the nano-microsphere dispersion, and the surfactant is 1-3% of the weight of the nano-microsphere dispersion; The nanospheres are selected from any one of organic polymer polymethyl methacrylate (PMMA) nanospheres, polystyrene (PS) nanospheres, poly(styrene-methyl methacrylate) (P(St-MMA)), poly(styrene-hydroxyethyl acrylate) (P(St-HEA)), poly(styrene-methacrylic acid) (P(St-MAA)), polystyrene@polydopamine (PS@PDA), polystyrene@silica (PS@SiO2) or inorganic silica (SiO2) nanospheres; The ultraviolet fluorescent printing paste is prepared by mixing an ultraviolet fluorescent response substance, a synthetic thickener and a soft segment and hard segment copolymerized waterborne polyurethane, wherein the amount of the ultraviolet fluorescent response substance is 6-10% by weight of the waterborne polyurethane, and the amount of the synthetic thickener is 0.5-1.0% by weight of the waterborne polyurethane; The ultraviolet fluorescent response substance is selected from fluorescent disperse dyes, fluorescent brighteners or fluorescein; The soft segment and hard segment copolymerized waterborne polyurethane is added in the form of aqueous dispersion with a mass fraction of 45-55%; S2, applying a screen printing method to scrape ultraviolet fluorescent printing paste on the surface of the hydrophobic fabric to prepare an ultraviolet fluorescent first anti-counterfeiting pattern with anti-counterfeiting information; S3, printing the slurry on the surface of the hydrophobic fabric having the first ultraviolet fluorescent anti-counterfeiting pattern obtained in S2 by screen printing to prepare a hydrophilic transparent pattern base layer and completely cover the first ultraviolet fluorescent anti-counterfeiting pattern; The slurry of the transparent pattern base layer is mixed with a synthetic thickener, a soft segment and hard segment copolymerized waterborne polyurethane or waterborne polyacrylate, and a hydrophilic substance, wherein the amount of the synthetic thickener is 0.5-1.0% by weight of the waterborne polyurethane or waterborne polyacrylate, and the amount of the hydrophilic substance is 0.5-2.5% by weight of the waterborne polyurethane or waterborne polyacrylate. The soft segment and hard segment copolymerized waterborne polyurethane or waterborne polyacrylate is added in the form of water dispersion with a mass fraction of 45-55%; The hydrophilic substance is one or a mixture of glycerol, ethylene glycol, propylene glycol, and urea; S4, applying a high mass fraction nano-microsphere color paste to the surface of the hydrophilic transparent pattern base layer obtained in S3 to prepare a second photonic crystal anti-counterfeiting pattern; S5, heating the fabric obtained in S4 to complete the assembly of nano-microspheres, activation and migration of the interface molecules of the polymer layer, secondary curing inside the photonic crystal structure, and stable curing of the photonic crystal structure, thereby obtaining a multi-anti-counterfeiting patterned photonic crystal structure color-forming fabric; In S2, the screen printing process is: a rubber scraper is scraped twice on a 100-150 mesh screen, dried at 80-90°C, and baked at 140-150°C for 1-2 minutes to obtain a UV fluorescent first anti-counterfeiting pattern with anti-counterfeiting information; in S3, the screen printing process is: a rubber scraper is scraped twice on a 100-150 mesh screen, dried at 80-90°C, and baked at 120-130°C for 1-2 minutes, and the prepared transparent pattern base layer must completely cover the first anti-counterfeiting pattern; The soft segment and hard segment copolymerized waterborne polyurethane, the hard segment is selected from one of toluene diisocyanate, isophorone diisocyanate, and 1,6-hexamethylene diisocyanate; the soft segment is a long carbon chain soft material with crystalline properties, the carbon chain length in the repeating unit is more than 4 C, and the soft segment is selected from one of poly(1,4-butylene adipate), poly(1,6-hexanediol adipate), and poly-1,6-hexamethylene carbonate; The water-based polyacrylate of the soft segment and hard segment copolymerization type, the hard segment is selected from one of methyl methacrylate, hydroxyethyl methacrylate or methyl acrylate, the soft segment is a long straight-chain monomer with more than 4 C, and the soft segment is selected from one of butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, and isooctyl acrylate; The melanin is one or a mixture of carbon black and water-soluble melanin; The surfactant is one or a mixture of polyoxyethylene sorbitan fatty acid ester, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty acid methyl ester ethoxylate or polypropylene glycol ethylene oxide adduct.

2. The method according to claim 1, characterized in that: The particle size of the nano-microspheres is 150-350 nm, and the monodispersity index is less than 0.

08.

3. The method according to claim 1, characterized in that: The heating treatment conditions in S5 are: temperature 50-70°C, humidity 50-70%, and time 3-60 min.

4. The method according to claim 1, characterized in that: The fabric is a natural fiber or a synthetic fiber or a blended fabric of several of them, the natural fiber includes cotton, linen, silk or wool, the synthetic fiber includes polyester, nylon, spandex, polypropylene, acrylic or polylactic acid, and the fabric is subjected to hydrophobic finishing; The finishing process of the hydrophobic fabric is as follows: the fabric is impregnated with a silicon-containing water-repellent finishing agent or a fluorine-containing water-repellent finishing agent at a concentration of 4-6% owf and a bath ratio of 1:15-25 for 15-20 minutes, squeezed dry, dried at 80-90°C, and baked at 140-150°C for 1-2 minutes to obtain a hydrophobic fabric.

5. The method according to claim 1, characterized in that: In S1, the components of the nano-microsphere printing paste and the ultraviolet fluorescent printing paste are mixed and then magnetically stirred at a speed of 20 r / s for 10 min to make them uniformly mixed.

6. The method according to claim 1, characterized in that: In S2, the screen printing process is: a rubber scraper is scraped twice on a 120-mesh screen, dried at 80°C, and baked at 140°C for 2 minutes; in S3, the screen printing process is: a rubber scraper is scraped twice on a 120-mesh screen, dried at 80°C, and baked at 120°C for 1 minute; in S5, the heating treatment conditions are: temperature 60°C, humidity 60%, and time 30 minutes.

7. The method according to claim 4, characterized in that: The finishing process of the hydrophobic fabric is as follows: the fabric is impregnated for 18 minutes under the conditions of fluorine-containing water-repellent finishing agent concentration of 5% owf and bath ratio of 1:20, squeezed dry, dried at 90° C., and baked at 140° C. for 2 minutes.

Citation Information

Patent Citations

  • Photonic crystal structure chromogenic fabric and preparation method thereof

    CN112323495A

  • Large-area preparation method of high-stability high-saturation photonic crystal structure yarn-producing fabric

    CN114164661A

  • Method for preparing patterned photonic crystal structure yarn-producing fabric with iridescent effect through screen printing method

    CN115287919A

  • Textile anticounterfeit printing method

    CN1743545A

Cited By

  • Structural coloring cooling fabric based on bionic photonic crystals

    CN117845615A